Manufacturing method of electronic device
Patent Information
- Application Number
- JP2023524243
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-28
- Filing Date
- 2022-05-27
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2042-05-27
AI Technical Summary
【0012】 本発明の電子装置の製造方法により、バックグラインド工程後において、ウエハ(または個片化されたチップ)から粘着性フィルムを剥離する際の糊残りを抑制することが可能となる。
Smart Images

Figure 0007630616000002 
Figure 0007630616000003 
Figure 0007630616000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing an electronic device. [Background technology]
[0002] 2. Description of the Related Art In the process of manufacturing electronic devices, in the process of grinding a wafer, an adhesive film is sometimes attached to the circuit-formed surface of the wafer in order to fix the wafer and prevent the wafer from being damaged. As such an adhesive film, a film in which an adhesive resin layer is laminated on a base film is generally used.
[0003] With the advancement of high-density mounting technology, there is a demand for thinner semiconductor wafers, for example, by grinding the wafer to a thickness of 50 μm or less. As one of such thin grinding processes, there is a pre-dicing method in which a groove of a predetermined depth is formed on one side of the wafer before grinding the wafer, and then the wafer is divided into individual pieces by grinding. There is also a pre-stealth method in which a modified region is formed by irradiating a laser inside the wafer before grinding, and then the wafer is divided into individual pieces by grinding.
[0004] Examples of technologies relating to adhesive films suitable for application to such dicing-first and stealth-first methods include the technologies described in Patent Document 1 (JP 2014-75560 A) and Patent Document 2 (JP 2016-72546 A).
[0005] Patent Document 1 describes a surface protection sheet having a pressure-sensitive adhesive layer on a substrate, which satisfies the following requirements (a) to (d). (a) The Young's modulus of the base material is 450 MPa or more. (b) The pressure-sensitive adhesive layer has a storage modulus of 0.10 MPa or more at 25°C. (c) The pressure-sensitive adhesive layer has a storage modulus of 0.20 MPa or less at 50°C. (d) The thickness of the adhesive layer is 30 μm or more. Patent document 1 describes that such a surface protection sheet can prevent contamination of the protected surface of the workpiece by suppressing the infiltration of water (sludge infiltration) into the gap formed when the workpiece is split during the back grinding process.
[0006] Patent Document 2 describes an adhesive tape for protecting the surface of a semiconductor wafer, which comprises a base resin film and a radiation-curable adhesive layer formed on at least one side of the base resin film, the base resin film having at least one rigid layer having a tensile modulus of elasticity of 1 to 10 GPa, and the adhesive layer having a peel force of 0.1 to 3.0 N / 25 mm at a peel angle of 30° after being radiation-cured. Patent Document 2 describes that such an adhesive tape for protecting the surface of a semiconductor wafer suppresses kerf shift of individualized semiconductor chips during the back grinding process of a semiconductor wafer using the first dicing method or the first stealth method, and enables the semiconductor wafer to be processed without being damaged or contaminated. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2014-75560 A [Patent Document 2] JP 2016-72546 A Summary of the Invention [Problem to be solved by the invention]
[0008] According to the study by the present inventors, for example, in the manufacturing process of electronic devices, when peeling off an adhesive film from a wafer after a back-grinding process, it has become clear that adhesive residue is likely to be left on the dicing street (scribe line) on the wafer side. In particular, in the manufacturing process of electronic devices using a first dicing method or a first stealth method, it has become clear that when peeling off an adhesive film from a wafer (diced chip) after a back-grinding process, adhesive residue is likely to be left on the wafer side. Specifically, in the first dicing method, an adhesive film is attached to one side of a wafer that has grooves on one side, so adhesive residue is likely to occur in the grooves and / or near the grooves. In particular, the grooves are usually cut using a blade, so they are prone to minute chips, which is thought to be one of the causes of adhesive residue. Even in the previous stealth method, it is thought that adhesive residue is likely to remain on the edges of the chips when the adhesive film is peeled off from the individualized wafer (chips).
[0009] The present invention has been made in view of the above circumstances. One of the objects of the present invention is to suppress "adhesive residue" when peeling an adhesive film from a wafer (or individual chips) after a back-grinding process in the manufacture of electronic devices. [Means for solving the problem]
[0010] The present inventors have investigated improvements from various perspectives, and as a result have completed the invention provided below, which has solved the above-mentioned problems. The present invention is as follows.
[0011] 1. A step (A) of preparing a structure including a wafer having a circuit formation surface and an adhesive film attached to the circuit formation surface side of the wafer; A step (B) of back-grinding the surface of the wafer opposite to the circuit-forming surface; (C) irradiating the adhesive film with ultraviolet light and then removing the adhesive film from the wafer; A method for manufacturing an electronic device comprising at least The adhesive film comprises a base layer and an adhesive resin layer made of an ultraviolet-curable adhesive resin material and provided on one surface side of the base layer; When the viscoelastic properties of the ultraviolet-curable adhesive resin material are measured by the following procedures (i) and (ii), the storage modulus at -15°C is E'(-15°C) and the storage modulus at 100°C is E'(100°C), E'(100℃) is 1.0×10 6 ~3.5×10 7 Pa, E'(100℃) / E'(-15℃) is 2.0×10 -3 ~1.5×10 -2 The method for manufacturing an electronic device is as follows. [procedure] (i) A film having a thickness of 0.2 mm is formed using the ultraviolet-curable adhesive resin material, and the film is irradiated with ultraviolet light having a dominant wavelength of 365 nm at an irradiation intensity of 100 W / cm using a high-pressure mercury lamp in an environment of 25°C. 2 The UV radiation level is 1080mJ / cm 2 The composition is then irradiated with UV light to cure the composition, thereby obtaining a cured film. (ii) The dynamic viscoelasticity of the cured film is measured at a frequency of 1 Hz in a tensile mode at a temperature range of -50 to 200°C. 2. A method for manufacturing the electronic device according to claim 1, comprising the steps of: E'(-15℃) is 6.0×10 8 ~3.0×10 9 A method for manufacturing an electronic device, 3. A method for producing an electronic device according to claim 1 or 2, comprising the steps of: The step (A) At least one step (A1) selected from a step (A1-1) of half-cutting the wafer and a step (A1-2) of irradiating the wafer with a laser to form a modified layer on the wafer; After the step (A1), a step (A2) of attaching the adhesive film to the circuit-formed surface side of the wafer; A method for manufacturing an electronic device comprising the steps of: 4. A method for manufacturing an electronic device according to any one of 1. to 3., In the step (C), the adhesive film is subjected to 200 mJ / cm 2 More than 2000mJ / cm 2 The adhesive resin layer is photocured by irradiating it with ultraviolet light at a dose below 100 nm to reduce the adhesive strength of the adhesive resin layer, and then the adhesive film is removed from the wafer. 5. A method for producing an electronic device according to any one of 1. to 4., The adhesive resin layer comprises a (meth)acrylic resin having a polymerizable carbon-carbon double bond in the molecule, and a photoinitiator. 6. A method for producing an electronic device according to any one of 1. to 5., The method for producing an electronic device, wherein the adhesive resin layer has a thickness of 5 μm or more and 300 μm or less. 7. A method for producing an electronic device according to any one of 1. to 6., A method for manufacturing an electronic device, wherein the resin constituting the base layer contains one or more selected from the group consisting of polyolefin, polyester, polyamide, poly(meth)acrylate, polyvinyl chloride, polyvinylidene chloride, polyimide, polyetherimide, ethylene-vinyl acetate copolymer, polyacrylonitrile, polycarbonate, polystyrene, ionomer, polysulfone, polyethersulfone, polyetheretherketone and polyphenylene ether. Effect of the Invention
[0012] The method for manufacturing an electronic device of the present invention makes it possible to suppress adhesive residue when peeling an adhesive film from a wafer (or individualized chips) after a backgrinding process. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a schematic diagram (cross-sectional view) showing an example of the structure of an adhesive film. [Diagram 2] 1A to 1C are diagrams (cross-sectional views) illustrating an example of a method for manufacturing an electronic device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. In all drawings, similar components are given similar symbols and descriptions thereof are omitted where appropriate. In order to avoid complexity, (i) when there are multiple identical components in the same drawing, only one of them will be given a symbol, and not all of them, or (ii) especially in Figure 2 and subsequent figures, components similar to those in Figure 1 will not be given a symbol again. All drawings are for illustrative purposes only. The shapes and dimensional ratios of each component in the drawings do not necessarily correspond to the actual objects.
[0015] In this specification, unless otherwise specified, the expression "X to Y" in the explanation of a numerical range means from X to Y. For example, "1 to 5% by mass" means "from 1% by mass to 5% by mass".
[0016] In the description of groups (atomic groups) in this specification, when a description is made without specifying whether the group is substituted or unsubstituted, the description includes both groups having no substituents and groups having a substituent. For example, an "alkyl group" includes not only an alkyl group having no substituents (unsubstituted alkyl group) but also an alkyl group having a substituent (substituted alkyl group). In this specification, the term "(meth)acrylic" refers to a concept that includes both acrylic and methacrylic. The same applies to similar terms such as "(meth)acrylate." In this specification, the term "organic group" means an atomic group obtained by removing one or more hydrogen atoms from an organic compound, unless otherwise specified. For example, a "monovalent organic group" refers to an atomic group obtained by removing one hydrogen atom from any organic compound. In this specification, the term "electronic device" is used to include elements, devices, final products, etc. to which electronic engineering technology is applied, such as semiconductor chips, semiconductor elements, printed wiring boards, electric circuit display devices, information and communication terminals, light-emitting diodes, physical batteries, and chemical batteries.
[0017] FIG. 1 is a cross-sectional view showing a schematic example of the structure of an adhesive film (adhesive film 50) preferably used in this embodiment. An adhesive film 50 is used to protect the surface of the wafer. As shown in FIG. 1, the adhesive film 50 includes a base layer 10 and an ultraviolet-curable adhesive resin layer 20 (an adhesive resin layer made of an ultraviolet-curable adhesive resin material) provided on one side of the base layer 10.
[0018] The adhesive resin layer 20 (adhesive resin layer made of an ultraviolet-curable adhesive resin material) has a storage modulus of elasticity at -15°C as E'(-15°C) and at 100°C as E'(100°C) when the viscoelastic properties are measured by the following procedures (i) and (ii). In this case, E'(100°C) and E'(100°C) / E'(-15°C) satisfy the following: E'(100℃):1.0×10 6 ~3.5×10 7 Pa E'(100℃) / E'(-15℃):2.0×10 -3 ~1.5×10 -2
[0019] [procedure] (i) A film having a thickness of 0.2 mm is formed using an ultraviolet-curing adhesive resin material, and the film is irradiated with ultraviolet light having a dominant wavelength of 365 nm at an irradiation intensity of 100 W / cm using a high-pressure mercury lamp in an environment of 25°C. 2 The UV radiation level is 1080mJ / cm 2 The composition is then irradiated with UV light to cure the composition, thereby obtaining a cured film. (ii) The dynamic viscoelasticity of the cured film is measured at a frequency of 1 Hz in a tensile mode at a temperature range of -50 to 200°C.
[0020] Moreover, E'(-15°C) is preferably in the following range. E'(-15℃):6.0×10 8 ~3.0×10 9 Pa
[0021] Incidentally, in order to suppress polymerization inhibition due to oxygen, the film formed using the ultraviolet-curable adhesive resin material is, for example, in a state of being attached to a release film during the ultraviolet irradiation in the above (i). Specifically, the following is done. A 0.2 mm thick ultraviolet-curable adhesive resin material having the same composition as the adhesive resin layer 20 is prepared. The ultraviolet-curable adhesive resin material is sandwiched between the silicone release-treated surfaces of a colorless, transparent polyethylene terephthalate film (separator) that has been treated with silicone release treatment on both sides. Examples of colorless, transparent polyethylene terephthalate films (separators) that have been treated with silicone release treatment include SP-PET T15 and T18 manufactured by Mitsui Chemicals Tohcello, and Purex A31 and A41 manufactured by Toyobo. The obtained sample (a three-layer structure of separator / adhesive resin layer 20 / separator) was irradiated with ultraviolet light of a dominant wavelength of 365 nm at an irradiation intensity of 100 W / cm using a high-pressure mercury lamp in an environment of 25°C. 2 The UV radiation level is 1080mJ / cm 2 Irradiate with UV light to harden. After UV curing, remove the separators on both sides to prepare a measurement sample, which is 10 mm wide and 50 mm long. Using a solid viscoelasticity measuring device, set the chuck distance to 20 mm, and measure the viscoelasticity at a frequency of 1 Hz, in tension mode, and in a temperature range of -50 to 200°C. An example of a solid viscoelasticity measuring device is the RSA3 manufactured by TA Instruments.
[0022] The lower limit of E'(-15°C) is more preferably 7.0 x 10 8 The upper limit of E'(-15°C) is more preferably 2.0 x 10 9The following is the result. The lower limit of E'(100°C) is preferably 5.0×10 6 The upper limit of E'(100°C) is preferably 2.0×10 7 The following is the result. The value of E'(-15°C) / E'(100°C) is preferably 3.0 x 10 -3 ~1.5×10 -2 The range is.
[0023] The relationship between the above-mentioned viscoelastic properties and the suppression of adhesive residue can be explained as follows. Just to be clear, the present invention is not limited to the following description.
[0024] Regarding the dynamic viscoelasticity of polymers, it is known that the frequency change is very similar to the temperature change, and that increasing the frequency and decreasing the temperature have similar effects (time-temperature conversion law). When the adhesive film is peeled off, the cured film of the adhesive resin layer is instantaneously and greatly deformed. Therefore, it is considered that the viscoelastic behavior in the high frequency region (i.e., low temperature region) corresponds well to the actual peeling state. In addition, based on the inventors' past findings, it is considered that the viscoelastic behavior in the low frequency region (i.e., high temperature region) reflects the crosslinking state of the cured film of the adhesive resin layer. The adhesive film after curing is usually peeled off at room temperature, but it is presumed that the storage modulus at a high temperature of about 100°C and the ratio E'(100°C) / E'(-15°C) of (storage modulus at a low temperature of about -15°C) to (storage modulus at a high temperature of about 100°C) are closely related to the peeling behavior. More specifically, it is as follows.
[0025] Regarding the elastic modulus at 100°C: 100°C is a temperature that is sufficiently high relative to the glass transition temperature of the adhesive, and it is believed that the non-crystalline adhesive is in a completely amorphous state. Therefore, E'(100°C) is believed to indicate the crosslink density of the adhesive. If E'(100°C) is too high, the crosslink density of the adhesive is too high, which significantly impairs toughness and makes the adhesive brittle and prone to breakage, presumably resulting in adhesive residue. If E'(100°C) is too low, this means that the crosslink density is too low, and the interaction between the adhesive and the adherend is too strong, making it difficult to peel off, presumably resulting in adhesive residue. Regarding the elastic modulus at low temperatures: Frequency changes are very similar to temperature changes, and it is known that increasing the frequency and decreasing the temperature have similar effects (time-temperature conversion law). It is known that the adhesive undergoes instantaneous large deformation during tape peeling, and it is believed that the viscoelastic behavior in the higher frequency range (i.e., lower temperature range) is closer to the actual peeling mode. Tape peeling is usually performed at room temperature, so the influence of the storage modulus E' at lower temperatures, for example -15°C, is considered. It is also presumed that if the ratio of E' (100°C) and E' (-15°C) mentioned above is within a certain range, peeling will proceed smoothly and adhesive will not easily remain. That is, if E'(100°C) / E'(-15°C) is too low, E'(-15°C) is relatively high, and it is presumed that the adhesive is too hard when actually peeled off, making it brittle and prone to breakage and leaving adhesive residue. Conversely, if E'(100°C) / E'(-15°C) is too high, E'(-15°C) is relatively small, and the adhesive is too soft when actually peeled off, resulting in high interaction between the adhesive and the adherend, making peeling difficult and prone to leaving adhesive residue.
[0026] In conclusion, it is presumed that a moderate value of E'(100°C) corresponds to the adhesive having a moderate crosslink density that is less likely to leave behind adhesive residue, and that a moderate value of E'(100°C) / E'(-15°C) corresponds to the adhesive having a moderate crosslink density and toughness, both of which contribute to reducing adhesive residue.
[0027] For reference, E'(-15℃) is also estimated. Regarding the elastic modulus at -15°C: It is known that frequency changes are very similar to temperature changes, and that increasing the frequency and decreasing the temperature have similar effects (time-temperature conversion law). It is known that the adhesive undergoes instantaneous and large deformation when the tape is peeled off, and it is believed that the viscoelastic behavior in the higher frequency range (i.e., lower temperature range) is closer to the actual peeling mode. Therefore, although tape peeling is usually performed at room temperature, it is presumed that the storage modulus E' at the lower temperature of -15°C closely represents the behavior of the adhesive when the tape is actually peeled off. For this reason, it is presumed that by designing the adhesive so that E' (-15°C) is an appropriate value, it is possible to further suppress adhesive residue.
[0028] The adhesive film 50 that satisfies the above-mentioned storage modulus requirement can be manufactured by appropriately selecting the materials, the appropriate blending of the materials, the manufacturing conditions, etc. The details of these will be described below from time to time.
[0029] In the section "1. Adhesive Film" below, each layer constituting the adhesive film 50 will be specifically described.
[0030] 1. Adhesive film (base material layer) The base layer 10 is a layer provided for the purpose of improving the properties of the adhesive film 50, such as handleability, mechanical properties, and heat resistance. The base layer 10 is not particularly limited as long as it has a mechanical strength sufficient to withstand the external force applied when processing the wafer, and examples thereof include a resin film. Examples of resins constituting the base layer 10 include one or more selected from polyolefins such as polyethylene, polypropylene, poly(4-methyl-1-pentene), poly(1-butene), etc.; polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.; polyamides such as nylon-6, nylon-66, polymetaxylene adipamide, etc.; (meth)acrylic resins such as polyacrylate and polymethacrylate; polyvinyl chloride; polyvinylidene chloride; polyimide; polyetherimide; ethylene-vinyl acetate copolymer; polyacrylonitrile; polycarbonate; polystyrene; ionomer; polysulfone; polyethersulfone; polyetheretherketone; polyphenylene ether, etc. Among these, from the viewpoint of improving mechanical properties and transparency, one or more selected from the group consisting of polypropylene, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide, ethylene-vinyl acetate copolymer, and polybutylene terephthalate are preferred, and one or more selected from polyethylene terephthalate and polyethylene naphthalate are more preferred.
[0031] The substrate layer 10 may be a single layer or two or more layers. The resin film used to provide the base layer 10 may be in the form of a stretched film or a uniaxially or biaxially stretched film. From the viewpoint of improving the mechanical strength of the base layer 10, a uniaxially or biaxially stretched film is preferable. From the viewpoint of suppressing warpage of the wafer after grinding, it is preferable that the base layer 10 is annealed in advance. The base layer 10 may be subjected to a surface treatment in order to improve adhesion to other layers. Specifically, corona treatment, plasma treatment, undercoat treatment, primer coat treatment, etc. may be performed.
[0032] From the viewpoint of obtaining good film properties, the thickness of the base layer 10 is preferably from 20 μm to 250 μm, more preferably from 30 μm to 200 μm, and even more preferably from 50 μm to 150 μm.
[0033] (Adhesive resin layer) The adhesive film 50 includes an ultraviolet-curing adhesive resin layer 20 . The adhesive resin layer 20 is a layer provided on one surface of the base layer 10, and is a layer that comes into contact with and adheres to the circuit-formed surface of the wafer when the adhesive film 50 is attached to the circuit-formed surface of the wafer.
[0034] The adhesive resin layer 20 is formed using an appropriate ultraviolet-curable adhesive resin material. Specifically, the adhesive resin layer 20 is formed using an ultraviolet-curable adhesive resin material whose adhesive strength decreases when exposed to ultraviolet light. When the adhesive resin layer 20 is irradiated with ultraviolet light, it hardens (crosslinks, etc.) and the adhesive strength decreases, so that the wafer (or chips obtained by dividing the wafer) can be easily peeled off from the adhesive film 50.
[0035] The ultraviolet-curable adhesive resin material preferably contains a (meth)acrylic resin known in the field of adhesives and bonding agents. Examples of the (meth)acrylic resin include homopolymers of (meth)acrylic acid ester compounds, copolymers of (meth)acrylic acid ester compounds and comonomers, etc. Examples of the (meth)acrylic acid ester compounds that are raw material monomers include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate. These (meth)acrylic acid ester compounds may be used alone or in combination of two or more. Examples of comonomers constituting the (meth)acrylic copolymer include vinyl acetate, (meth)acrylonitrile, styrene, (meth)acrylic acid, itaconic acid, (meth)acrylamide, methylol (meth)acrylamide, maleic anhydride, etc. When using these comonomers, they may be used alone or in combination of two or more.
[0036] The ultraviolet-curable adhesive resin material preferably contains a (meth)acrylic resin having a polymerizable carbon-carbon double bond at a side chain and / or at an end, a photoinitiator, and further contains a crosslinking agent, etc., as necessary. The ultraviolet-curable adhesive resin material may further contain a low-molecular-weight compound (such as a polyfunctional (meth)acrylate compound) having two or more polymerizable carbon-carbon double bonds in one molecule.
[0037] Specifically, a (meth)acrylic resin having a polymerizable carbon-carbon double bond in a side chain and / or at a terminal is obtained as follows. First, a monomer having an ethylenic double bond and a copolymerizable monomer having a functional group (P) are copolymerized. Next, the functional group (P) contained in this copolymer is reacted with a monomer having a functional group (Q) capable of undergoing an addition reaction, a condensation reaction, or the like with the functional group (P) while leaving the double bond in the monomer, thereby introducing a polymerizable carbon-carbon double bond into the copolymer molecule.
[0038] As the monomer having an ethylenic double bond, one or more of the following may be used: alkyl acrylate and alkyl methacrylate monomers, such as methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, butyl (meth)acrylate, and ethyl (meth)acrylate; vinyl esters, such as vinyl acetate; (meth)acrylonitrile, (meth)acrylamide; and monomers having an ethylenic double bond, such as styrene.
[0039] Examples of copolymerizable monomers having a functional group (P) include (meth)acrylic acid, maleic acid, 2-hydroxyethyl (meth)acrylate, glycidyl (meth)acrylate, N-methylol (meth)acrylamide, (meth)acryloyloxyethyl isocyanate, etc. These may be used alone or in combination of two or more. The ratio of the monomer having an ethylenic double bond to the copolymerizable monomer having a functional group (P) is preferably 70 to 99 mass % of the monomer having an ethylenic double bond and 1 to 30 mass % of the copolymerizable monomer having a functional group (P), and more preferably 80 to 95 mass % of the monomer having an ethylenic double bond and 5 to 20 mass % of the copolymerizable monomer having a functional group (P). Examples of the monomer having the functional group (Q) include the same monomers as the copolymerizable monomer having the functional group (P).
[0040] As a combination of functional group (P) and functional group (Q) to be reacted when introducing a polymerizable carbon-carbon double bond into a copolymer of a monomer having an ethylenic double bond and a copolymerizable monomer having a functional group (P), a combination that easily causes an addition reaction is desirable, such as a carboxyl group and an epoxy group, a carboxyl group and an aziridinyl group, a hydroxyl group and an isocyanate group, etc. In addition to the addition reaction, any reaction that easily introduces a polymerizable carbon-carbon double bond, such as a condensation reaction between a carboxylic acid group and a hydroxyl group, can be applied. When a monomer having an ethylenic double bond and a copolymerizable monomer having a functional group (P) are copolymerized, a polymerization initiator can be used. Examples of the polymerization initiator include radical polymerization initiators such as benzoyl peroxide-based polymerization initiators and t-butylperoxy-2-ethylhexanoate.
[0041] Examples of low molecular weight compounds having two or more polymerizable carbon-carbon double bonds in one molecule include polyfunctional (meth)acrylate compounds such as tripropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetraacrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane tetraacrylate. When using these, only one type may be used, or two or more types may be used. The amount of the low molecular weight compound having two or more polymerizable carbon-carbon double bonds in the molecule is preferably 0.1 to 20 parts by mass, more preferably 5 to 18 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin. The amount of the low molecular weight compound having two or more polymerizable carbon-carbon double bonds in the molecule is preferably 0.1 part by mass or more, more preferably 1 part by mass or more, even more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic resin, and is preferably 20 parts by mass or less, more preferably 18 parts by mass or less, even more preferably 15 parts by mass or less, and even more preferably 13 parts by mass or less.
[0042] A photoinitiator is generally a compound that generates chemical species (such as radicals) that polymerize polymerizable carbon-carbon double bonds when irradiated with ultraviolet light. Examples of photoinitiators include benzoin, isopropyl benzoin ether, isobutyl benzoin ether, benzophenone, Michler's ketone, chlorothioxanthone, dodecyl thioxanthone, dimethyl thioxanthone, diethyl thioxanthone, acetophenone diethyl ketal, benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2-benzyl-2-dimethylamino-4'-morpholinobutyrophenone, 2,2-dimethoxy-2-phenylacetophenone, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)butan-1-one, and the like.
[0043] The photoinitiator may be used alone or in combination of two or more kinds. The amount of the photoinitiator added is preferably 0.1 to 15 parts by mass, more preferably 1 to 10 parts by mass, and even more preferably 4 to 10 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin. The amount of the photoinitiator added is, relative to 100 parts by mass of the (meth)acrylic resin, preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, even more preferably 3 parts by mass or more, even more preferably 4 parts by mass or more, even more preferably 5 parts by mass or more, and is preferably 15 parts by mass or less, more preferably 12 parts by mass or less, even more preferably 10 parts by mass or less, and even more preferably 8 parts by mass or less.
[0044] The ultraviolet-curable adhesive resin material may contain a crosslinking agent. Examples of the crosslinking agent include epoxy compounds such as sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, and diglycerol polyglycidyl ether; aziridine compounds such as tetramethylolmethane-tri-β-aziridinyl propionate, trimethylolpropane-tri-β-aziridinyl propionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide); and isocyanate compounds such as tetramethylene diisocyanate, hexamethylene diisocyanate, and polyisocyanate. The crosslinking agent may be used alone or in combination of two or more kinds.
[0045] When a crosslinking agent is used, the amount is usually preferably within a range in which the number of functional groups in the crosslinking agent is not greater than the number of functional groups in the (meth)acrylic resin, but may be contained in excess as necessary when new functional groups are generated by the crosslinking reaction or when the crosslinking reaction is slow. When a crosslinking agent is used, the content of the crosslinking agent in the ultraviolet-curable adhesive resin material is preferably 0.1 parts by mass or more and 15 parts by mass or less, and more preferably 0.5 parts by mass or more and 5 parts by mass or less, per 100 parts by mass of the (meth)acrylic resin, from the viewpoint of improving the balance between the heat resistance and adhesion of the adhesive resin layer 20. In addition, when a crosslinking agent is used, the content of the crosslinking agent in the ultraviolet-curable adhesive resin material is, from the viewpoint of improving the balance between the heat resistance and adhesion of the adhesive resin layer 20, preferably 0.1 part by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.5 parts by mass or more, even more preferably 0.7 parts by mass or more, and is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic resin.
[0046] The adhesive resin layer 20 can be formed, for example, by applying an ultraviolet-curable adhesive resin material onto one surface of the base layer 10. That is, the adhesive resin layer 20 can be provided by applying an ultraviolet-curable adhesive resin material prepared by dissolving or dispersing each of the above components in an appropriate solvent (typically an organic solvent) onto one surface of the base layer 10. Examples of the coating method include roll coater, reverse roll coater, gravure roll, bar coat, comma coater, and die coater. There are no particular limitations on the drying conditions, but generally, drying is preferably performed for 10 seconds to 10 minutes at a temperature range of 80 to 200°C. More preferably, drying is performed for 15 seconds to 5 minutes at 80 to 170°C. In order to sufficiently promote the crosslinking reaction between the crosslinking agent and the (meth)acrylic resin, the adhesive coating liquid may be heated at 40 to 80°C for about 5 to 300 hours after drying is completed.
[0047] As an alternative to applying an ultraviolet-curable adhesive resin material onto one side of the base layer 10, there can also be mentioned a method in which, as shown in the examples below, (i) first, an ultraviolet-curable adhesive resin material is applied to the surface of an easily peelable base material (separator) to form an adhesive resin layer 20, and then (ii) the formed adhesive resin layer is bonded to one side of the base layer 10.
[0048] The thickness of the adhesive resin layer 20 is preferably 5 μm or more and 300 μm or less, more preferably 10 μm or more and 100 μm or less, and further preferably 10 μm or more and 50 μm or less. The thickness of the adhesive resin layer 20 is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, and is preferably 300 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less. Sufficient adhesiveness can be obtained by making the adhesive resin layer 20 appropriately thick. Also, the adhesive resin layer 20 is not too thick, so that the handleability of the adhesive film 50 is improved.
[0049] (Other layers) The adhesive film 50 may have other layers as long as the effect of suppressing adhesive residue is not impaired. For example, other layers such as an irregularity-absorbing resin layer, an adhesive layer, and an antistatic layer may be provided between each layer. By providing an irregularity-absorbing resin layer, the irregularity absorption of the adhesive film 50 can be improved. By providing an adhesive layer, the adhesion between each layer can be improved. Furthermore, by providing an antistatic layer, the antistatic property of the adhesive film 50 can be improved. In order to prevent deterioration or adhesion of foreign matter before use, the exposed surface of the adhesive resin layer 20 may be protected with an appropriate protective film (easily peelable film) such as a release film.
[0050] (Overall thickness) The total thickness of the adhesive film 50 is preferably 50 μm or more and 600 μm or less, more preferably 50 μm or more and 400 μm or less, and even more preferably 50 μm or more and 300 μm or less, in terms of the balance between mechanical properties and handling properties.
[0051] (Adhesive strength decreases due to exposure to ultraviolet rays) As described above, in the adhesive film 50, the adhesive resin layer 20 is formed using an ultraviolet-curable adhesive resin material whose adhesive strength decreases when exposed to ultraviolet light. The degree to which adhesion is reduced by ultraviolet light is preferably quantified as follows.
[0052] The adhesive resin layer 20 of the adhesive film 50 is bonded to a mirror-polished silicon wafer, and after leaving it for 1 hour, a peel test is performed under the conditions of a peel angle of 180° and a peel speed of 300 mm / min. The peel strength is defined as F0. The adhesive resin layer 20 of the adhesive film 50 is bonded to a mirror-polished silicon wafer, and ultraviolet rays having a wavelength of 365 nm are irradiated at 1080 mJ / cm 2 After irradiation, a peel test was carried out under conditions of a peel angle of 180° and a peel speed of 300 mm / min. The peel strength measured was designated as F1. ·F1 / F0 is preferably 0.01 to 0.60, more preferably 0.01 to 0.20, and further preferably 0.02 to 0.20. Furthermore, F1 / F0 is preferably 0.01 or more, more preferably 0.015 or more, more preferably 0.02 or more, and is preferably 0.60 or less, more preferably 0.30 or less, even more preferably 0.20 or less, even more preferably 0.15 or less, and even more preferably 0.12 or less.
[0053] By setting F1 / F0 to an appropriate value, the positional deviation of the wafer during the back-grinding process is suppressed, and the adhesive film 50 can be easily peeled off after the back-grinding process.
[0054] Incidentally, the value of F0 itself is, for example, 3 to 20 N / 25 mm, specifically, 3 to 16 N / 25 mm. The value of F1 itself is, for example, 10 N / 25 mm or less, specifically 1 N / 25 mm or less, more specifically 0.5 N / 25 mm or less. F1 may be zero, but F1 is usually 0.005 N / 25 mm or more, specifically 0.01 N / 25 mm or more.
[0055] 2. Manufacturing method of electronic device FIG. 2 is a cross-sectional view that illustrates an example of a method for manufacturing an electronic device using the adhesive film 50. As shown in FIG. The method for manufacturing an electronic device includes, for example, at least the following three steps. (A) A step of preparing a structure 100 including a wafer 30 having a circuit-forming surface 30A and an adhesive film 50 attached to the circuit-forming surface 30A side of the wafer 30. (B) a step of back-grinding the surface of the wafer 30 opposite the circuit formation surface 30A; (C) A step of removing the adhesive film 50 from the wafer 30 after irradiating the adhesive film 50 with ultraviolet light. In this series of steps, the adhesive film described above in the section "1. Adhesive Film" is used as the adhesive film 50. The method for manufacturing an electronic device according to this embodiment is characterized in that the adhesive film 50 is used as a so-called backgrind tape when grinding the back surface of the wafer 30. Each step of the method for manufacturing an electronic device will now be described.
[0056] (Process (A)) First, a structure 100 including a wafer 30 having a circuit-forming surface 30A and an adhesive film 50 attached to the circuit-forming surface 30A side of the wafer 30 is prepared. Such a structure 100 can be produced, for example, by peeling off a release film from the adhesive resin layer 20 of the adhesive film 50 to expose the surface of the adhesive resin layer 20, and attaching the circuit formation surface 30A of the wafer 30 onto the adhesive resin layer 20.
[0057] Here, the conditions for attaching the circuit-forming surface 30A of the wafer 30 to the adhesive film 50 are not particularly limited, but may be, for example, a temperature of 20 to 80° C., a pressure of 0.05 to 0.5 MPa, and an attachment speed of 0.5 to 20 mm / sec.
[0058] It is preferable that step (A) further includes at least one step (A1) selected from step (A1-1) of half-cutting wafer 30 and step (A1-2) of irradiating wafer 30 with a laser to form a modified layer on wafer 30, and, after step (A1), step (A2) of attaching an adhesive film 50 for backgrinding to the circuit formation surface 30A side of wafer 30. As described above, the adhesive film 50 according to this embodiment can be suitably used in the manufacturing process of electronic devices using a dicing-first method, a stealth-first method, etc. Therefore, a manufacturing method that performs the above-mentioned step (A1-1) which is a dicing-first method or the above-mentioned step (A1-2) which is a stealth-first method is preferable.
[0059] In step (A2), the adhesive film 50 can be heated and attached to the circuit formation surface 30A of the wafer 30. This makes it possible to maintain good adhesion between the adhesive resin layer 20 and the wafer 30 for a long period of time. The heating temperature is not particularly limited, but is, for example, 60 to 80°C.
[0060] The operation of attaching the adhesive film 50 to the wafer 30 may be performed manually, but generally, it can be performed by a device called an automatic attachment machine equipped with a roll of adhesive film.
[0061] The wafer 30 to be attached to the adhesive film 50 is not particularly limited, but is preferably a wafer 30 having a circuit formation surface 30A. Examples include a semiconductor wafer, an epoxy molded wafer, an epoxy molded panel, and the like, and the semiconductor wafer and the epoxy molded wafer are preferred. Examples of semiconductor wafers include silicon wafers, sapphire wafers, germanium wafers, germanium-arsenic wafers, gallium-phosphorus wafers, gallium-arsenic-aluminum wafers, gallium-arsenic wafers, lithium tantalate wafers, etc., and are preferably used for silicon wafers. Examples of epoxy mold wafers include wafers produced by the eWLB (Embedded Wafer Level Ball Grid Array) process, which is one of the methods for producing fan-out type WLPs. The semiconductor wafer and epoxy mold wafer having a circuit-forming surface are not particularly limited, and examples thereof include those having circuits such as wiring, capacitors, diodes, transistors, etc. formed on the surface. The circuit-forming surface may be subjected to plasma treatment.
[0062] The circuit formation surface 30A of the wafer 30 may be uneven due to the presence of bump electrodes or the like. For example, when mounting an electronic device on a mounting surface, the bump electrode is joined to an electrode formed on the mounting surface to form an electrical connection between the electronic device and the mounting surface (the mounting surface of a printed circuit board, etc.). Examples of the bump electrode include ball bumps, printed bumps, stud bumps, plated bumps, and pillar bumps. That is, the bump electrode is usually a convex electrode. These bump electrodes may be used alone or in combination of two or more types. The height and diameter of the bump electrodes are not particularly limited, but are preferably 10 to 400 μm, more preferably 50 to 300 μm, respectively. The bump pitch is also not particularly limited, but is preferably 20 to 600 μm, more preferably 100 to 500 μm. The metal species constituting the bump electrode is not particularly limited, and examples thereof include solder, silver, gold, copper, tin, lead, bismuth, and alloys thereof, but the adhesive film 50 is preferably used when the bump electrode is a solder bump. These metal species may be used alone or in combination of two or more.
[0063] (Process (B)) Next, the surface of the wafer 30 opposite to the circuit formation surface 30A (also called the back surface) is back-ground. "Back grinding" refers to thinning the wafer 30 to a predetermined thickness without damaging the wafer. For example, the structure 100 is fixed to a chuck table or the like of a grinding machine, and the back surface (surface on which no circuit is formed) of the wafer 30 is ground.
[0064] In such a back grinding operation, the wafer 30 is ground until its thickness becomes equal to or less than a desired thickness. The thickness of the wafer 30 before grinding is appropriately determined depending on the diameter, type, etc. of the wafer 30, and the thickness of the wafer 30 after grinding is appropriately determined depending on the size of the chip to be obtained, the type of circuit, etc. Furthermore, when the wafer 30 is half-cut or a modified layer is formed by laser irradiation, the wafer 30 is divided into individual chips 31 in step (B) as shown in FIG.
[0065] The back grinding method is not particularly limited, and any known grinding method can be used. Grinding can be performed while cooling the wafer 30 and the grindstone by pouring water on them. If necessary, a dry polishing process, which is a grinding method that does not use grinding water, can be performed at the end of the grinding process. After the back grinding is completed, chemical etching is performed as necessary. Chemical etching is performed by immersing the wafer 30 with the adhesive film 50 attached in an etching solution selected from the group consisting of an acidic aqueous solution consisting of a single or mixed solution of hydrofluoric acid, nitric acid, sulfuric acid, acetic acid, etc., an alkaline aqueous solution consisting of a potassium hydroxide aqueous solution, a sodium hydroxide aqueous solution, etc. Etching is performed for the purpose of removing distortion generated on the back surface of the wafer 30, further thinning the wafer 30, removing oxide films, etc., pretreatment when forming an electrode on the back surface, etc. The etching solution is appropriately selected depending on the above purpose.
[0066] (Process (C)) Next, the adhesive film 50 is irradiated with ultraviolet light, and then the adhesive film 50 is removed from the wafer 30. In step (C), the adhesive film 50 is irradiated with ultraviolet light of, for example, 200 mJ / cm 2 More than 2000mJ / cm 2 By irradiating the adhesive resin layer 20 with ultraviolet rays at the following dose, the adhesive resin layer 20 is ultraviolet-cured to reduce the adhesive strength of the adhesive resin layer 20, and then the adhesive film 50 is removed from the wafer 30. The ultraviolet irradiation can be carried out, for example, by using ultraviolet rays having a dominant wavelength of 365 nm from a high-pressure mercury lamp. The irradiation intensity of the ultraviolet light is, for example, 50 mW / cm 2 More than 500mW / cm 2 The following is the result.
[0067] Before removing the adhesive film from the wafer 30, the wafer 30 may be mounted on a dicing tape or a dicing tape with a die attach film together with a ring frame. The operation of removing the adhesive film 50 from the wafer 30 may be performed manually, but can generally be performed by a device called an automatic peeling machine. The surface of the wafer 30 after peeling off the adhesive film 50 may be washed as necessary. Examples of the washing method include wet washing such as water washing or solvent washing, and dry washing such as plasma washing. In the case of wet washing, ultrasonic washing may be used in combination. The washing method can be appropriately selected depending on the contamination state of the surface of the wafer 30.
[0068] (Other processes) After steps (A) to (C) are performed, a step of mounting the obtained chip 31 on a circuit board may be further performed. These steps can be performed based on publicly known information.
[0069] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0070] The embodiments of the present invention will be described in detail based on Examples and Comparative Examples. It should be noted that the present invention is not limited to the Examples. In the examples, exponential notation may be indicated by the symbol "E". For example, 1.3E+06 is expressed as 1.3 x 10 6 means.
[0071] <Preparation of raw materials> The following raw materials were prepared:
[0072] (base material layer) Base layer 1: Polyethylene terephthalate film (manufactured by Toyobo Co., Ltd., product name: E7180, thickness: 50 μm, one-sided corona treatment product)
[0073] Base layer 2: A laminated film (total thickness: 110 μm) consisting of a low-density polyethylene film / polyethylene terephthalate film / low-density polyethylene film, produced as follows. A polyethylene terephthalate film (manufactured by Toray Industries, product name: Lumirror S10, thickness: 50 μm) was attached to both sides of a low-density polyethylene film (density: 0.925 kg / m 3 One side of the obtained laminated film was subjected to corona treatment.
[0074] Base layer 3: A laminate film (total thickness: 145 μm) consisting of a polyethylene terephthalate film / ethylene-vinyl acetate copolymer film / acrylic film, produced as follows. A polyethylene terephthalate film (Toyobo Co., Ltd., product name: E7180, thickness: 50 μm) and an ethylene-vinyl acetate copolymer (Mitsui Dow Polychemicals Co., Ltd., MFR: 2.5 g / 10 min) film (thickness: 70 μm) were laminated by applying a corona discharge treatment to the bonding surface of the ethylene-vinyl acetate copolymer film with the polyethylene terephthalate film. In addition, the opposite surface of the ethylene-vinyl acetate copolymer film to the polyethylene terephthalate film was also subjected to a corona discharge treatment. Next, the release surface of a release-treated polyethylene terephthalate film (separator) was coated with the acrylic resin coating solution for the base layer shown below to a dry thickness of 20 μm, dried, and then laminated to the above-mentioned polyethylene terephthalate film / ethylene-vinyl acetate copolymer film laminate film via the ethylene-vinyl acetate copolymer film, and aged (40°C, 3 days).The separator was then peeled off. In this manner, the base layer 3 was obtained.
[0075] (Acrylic resin coating solution for base layer) Using 0.5 parts by mass of 4,4'-azobis-4-cyanovaleric acid (Otsuka Chemical Co., Ltd., product name: ACVA) as a polymerization initiator, 74 parts by mass of butyl acrylate, 14 parts by mass of methyl methacrylate, 9 parts by mass of 2-hydroxyethyl methacrylate, 2 parts by mass of methacrylic acid, 1 part by mass of acrylamide, and 3 parts by mass of an aqueous solution of polyoxyethylene nonylpropenyl phenyl ether ammonium sulfate (Dai-ichi Kogyo Seiyaku Co., Ltd., product name: Aqualon HS-1025) were emulsion-polymerized in deionized water at 70°C for 9 hours. After the polymerization was completed, the pH was adjusted to 7 with ammonia water to obtain an aqueous acrylic polymer emulsion with a solid content concentration of 42.5% by mass. Next, 100 parts by mass of this acrylic polymer aqueous emulsion was adjusted to pH 9 or higher using ammonia water, and 0.75 parts by mass of an aziridine-based crosslinking agent (ChemiTite PZ-33, manufactured by Nippon Shokubai Kagaku Kogyo Co., Ltd.) and 5 parts by mass of diethylene glycol monobutyl ether were added. In this manner, an acrylic resin coating liquid for the base layer was obtained.
[0076] ((Meth)acrylic resin solution) (Meth)acrylic resin solution 1: 49 parts by mass of ethyl acrylate, 20 parts by mass of 2-ethylhexyl acrylate, 21 parts by mass of methyl acrylate, 10 parts by mass of glycidyl methacrylate, and 0.5 parts by mass of a benzoyl peroxide-based polymerization initiator (solid content equivalent) were reacted in a mixed solvent of 65 parts by mass of toluene and 50 parts by mass of ethyl acetate at 80° C. for 10 hours. After the reaction was completed, the resulting solution was cooled, and 25 parts by mass of xylene, 5 parts by mass of acrylic acid, and 0.5 parts by mass of tetradecyldimethylbenzylammonium chloride were added to the cooled solution, and the reaction was carried out at 85° C. for 32 hours while blowing in air. In this manner, a (meth)acrylic resin solution 1 was obtained.
[0077] (Meth)acrylic resin solution 2: 77 parts by mass of n-butyl acrylate, 16 parts by mass of methyl methacrylate, 16 parts by mass of 2-hydroxyethyl acrylate, and 0.3 parts by mass of t-butylperoxy-2-ethylhexanoate as a polymerization initiator were reacted in a mixed solvent of 20 parts by mass of toluene and 80 parts by mass of ethyl acetate at 85° C. for 10 hours. After the reaction was completed, the resulting solution was cooled, and 30 parts by mass of toluene, 7 parts by mass of methacryloyloxyethyl isocyanate (manufactured by Showa Denko, product name: Karenz MOI), and 0.05 parts by mass of dibutyltin dilaurate were added thereto, and the mixture was reacted at 85° C. for 12 hours while blowing in air. In this manner, a (meth)acrylic resin solution 2 was obtained.
[0078] (Meth)acrylic resin solution 3: 30 parts by mass of ethyl acrylate, 11 parts by mass of methyl acrylate, 26 parts by mass of 2-ethylhexyl acrylate, 7 parts by mass of 2-hydroxyethyl methacrylate, and 0.8 parts by mass (solid content equivalent) of a benzoyl peroxide-based polymerization initiator as a polymerization initiator were reacted in a mixed solvent of 7 parts by mass of toluene and 50 parts by mass of ethyl acetate at 80° C. for 9 hours. After completion of the reaction, the obtained solution was cooled, and 25 parts by mass of toluene was added to the cooled solution. In this manner, a (meth)acrylic resin solution 3 was obtained.
[0079] (Photoinitiator) Omnirad 651 (IGM): 2,2-dimethoxy-2-phenylacetophenone Omnirad 369 (IGM): 2-benzyl-2-dimethylamino-4'-morpholinobutyrophenone
[0080] (Polyfunctional (meth)acrylate) Aronix M400 (manufactured by Toagosei Co., Ltd.): A mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate
[0081] (Crosslinking agent) Isocyanate-based crosslinking agent (manufactured by Mitsui Chemicals, product name: Olestar P49-75S)
[0082] <Preparation of UV-curable adhesive resin material (coating liquid for forming adhesive resin layer)> The materials listed in the "UV-curable adhesive resin material (coating liquid for forming adhesive resin layer)" column in Table 1 were mixed uniformly to obtain an UV-curable adhesive resin material (coating liquid for forming adhesive resin layer).
[0083] <Viscoelasticity measurement of cured film of UV-curable adhesive resin material> First, the ultraviolet-curable adhesive resin material (coating liquid for forming an adhesive resin layer) shown in Table 1 was applied to a polyethylene terephthalate film (separator) (Mitsui Chemicals Tohcello SP-PET T18 (thickness 31 μm)) that had been subjected to a silicone release treatment. Next, it was dried at 120°C for 3 minutes to form an adhesive resin layer with a thickness of 30 to 40 μm. Several layers of the obtained adhesive resin layers were stacked together to obtain a laminate sample having a separator / adhesive resin layer with a thickness of 0.2 mm / separator configuration. The obtained laminate sample was heated in an oven at 40°C for 3 days and aged. The obtained laminate sample (separator / adhesive resin layer / separator structure) was irradiated with ultraviolet light having a dominant wavelength of 365 nm using a high-pressure mercury lamp at an irradiation intensity of 100 W / cm in an environment of 25°C. 2 The UV radiation level is 1080mJ / cm 2 The resin was then irradiated with UV light for curing. Next, the viscoelasticity was measured using a solid viscoelasticity measuring device (TA Instruments, RSA3). Specifically, the cured laminate sample was cut to a width of 10 mm and a length of 50 mm, and the separators on both sides of the cured laminate sample were removed to obtain a measurement sample. The measurement sample was then set in the device so that the chuck distance was 20 mm. Then, the dynamic viscoelasticity was measured at a frequency of 1 Hz in tension mode at a temperature range of -50 to 200°C.
[0084] <Preparation of adhesive film> First, the ultraviolet-curable adhesive resin material (coating liquid for forming an adhesive resin layer) shown in Table 1 was applied to a polyethylene terephthalate film (separator) that had been subjected to a silicone release treatment, and then dried at 120°C for 3 minutes to form an adhesive resin layer with a thickness of 20 μm. The formed adhesive resin layer was attached to a base layer to form a laminate. Specifically, when base layer 1 or 2 was used as the base layer, it was attached to the corona-treated surface. When base layer 3 was used as the base layer, the separator was peeled off and it was attached to the acrylic film layer side. The resulting laminate was heated in an oven at 40° C. for 3 days and aged. In this manner, an adhesive film for backgrinding was obtained.
[0085] <Confirmation of basic physical properties> (1) Adhesive strength evaluation: Measurement of adhesive strength before and after UV irradiation (i) Preparation of adherend wafers for adhesion measurements: The mirror surface of a silicon mirror wafer (4-inch single-sided mirror wafer, manufactured by SUMCO) was ozone-cleaned (ozone treatment time: 60 seconds) using a UV ozone cleaning device (UV-208, manufactured by Technovision). After that, the wafer mirror surface was wiped with ethanol to prepare a substrate wafer.
[0086] (ii) Measurement of adhesion before UV irradiation: In an environment of 23°C and 50% RH, the adhesive film obtained in <Preparation of adhesive film> was cut to a width of 50 mm, the separator was peeled off, and the adhesive film was attached to the mirror surface of the adherend wafer via its adhesive resin layer using a hand roller. Then, it was left for 1 hour. After leaving it, one end of the adhesive film was clamped using a tensile tester (Shimadzu Corporation, product name: Autograph AGS-X), and the adhesive film was peeled off from the surface of the adherend wafer at a peel angle of 180° and a peel speed of 300 mm / min. The stress at this time was measured and converted to N / 25 mm to determine the adhesive strength. The evaluation was performed with N=2, and the average of the two values obtained was determined as the peel strength F0.
[0087] (iii) Measurement of adhesive strength after UV irradiation: Under an environment of 23°C and 50% RH, the adhesive film for adhesive strength evaluation was cut to a width of 50 mm, the separator was peeled off, and the adhesive film was attached to the mirror surface of the adherend wafer via its adhesive resin layer using a hand roller, and then left to stand for 1 hour. After leaving it, it was irradiated with ultraviolet light of 365 nm in wavelength using a high-pressure mercury lamp at an irradiation intensity of 100 mW / cm in an environment of 25°C. 2 The adhesive film is exposed to 1080mJ / cm of UV light. 2 The adhesive film was then irradiated. One end of the adhesive film was then clamped using a tensile tester (Shimadzu Corporation, product name: Autograph AGS-X), and the adhesive film was peeled off from the surface of the wafer at a peel angle of 180° and a peel speed of 300 mm / min. The stress at this time was measured and converted to N / 25 mm to determine the adhesive strength. The evaluation was performed with N=2, and the two values obtained were averaged to determine the peel strength F1. Then, F1 / F0 was calculated from the obtained F1 and F0 values.
[0088] (2) Evaluation of adhesive residue In the above (iii), the adherend wafer after the ultraviolet peeling was visually observed to judge whether or not there was adhesive residue. If no adhesive residue was observed, it was recorded as "none" in Table 1.
[0089] <Various evaluations of the pre-dicing method> (1) Preparation of evaluation wafer Evaluation wafer 1: Using a dicing saw, the mirror surface of a mirror wafer (KST World Corporation, 8-inch mirror wafer, diameter: 200±0.5 mm, thickness: 725±50 μm, one-sided mirror) was half-cut to obtain evaluation wafer 1. (Blade: ZH05-SD3500-N1-70-DD, chip size: 5 mm × 8 mm, cutting depth: 58 μm, blade rotation speed: 30,000 rpm). When evaluation wafer 1 was observed with an optical microscope, the kerf width was 35 μm.
[0090] Evaluation wafer 2: Using a dicing saw, a first half cut was performed on the mirror surface of a mirror wafer (KST World Corporation, 8-inch mirror wafer, diameter: 200±0.5 mm, thickness: 725±50 μm, one-sided mirror) (blade: Z09-SD2000-Y1 58×0.25A×40×45E-L, chip size: 5 mm×8 mm, cutting depth: 15 μm, blade rotation speed: 30000 rpm). When observed with an optical microscope, the kerf width was 60 μm. Next, a second half cut was performed (blade: ZH05-SD3500-N1-70-DD, chip size: 5 mm×8 mm, cutting depth: 58 μm, blade rotation speed: 30000 rpm) to obtain evaluation wafer 2.
[0091] (2) Implementation of pre-dicing method and various evaluations Using a tape laminator (DR3000II, manufactured by Nitto Denko Corporation), an adhesive film was attached to the half-cut surface of the evaluation wafer (evaluation wafer 1 or 2) (23° C., attachment speed: 5 mm / sec, attachment pressure: 0.36 MPa). Next, the wafer was back-ground using a grinder (DISCO Corporation, DGP8760) (rough grinding and precision grinding, precision grinding amount: 40 μm, no polishing, thickness after grinding: 38 μm) and divided into individual pieces.
[0092] After that, UV irradiation and peeling of the adhesive film were performed to evaluate the device peelability and adhesive residue after the pre-dicing method. Specifically, UV irradiation was performed using a high-pressure mercury lamp at a temperature of 25°C, with ultraviolet light of a dominant wavelength of 365 nm and an irradiation intensity of 100 mW / cm. 2 The adhesive film is exposed to 1080mJ / cm of UV light. 2 was irradiated. The adhesive film was peeled off in the following manner. First, a dicing tape (used as a mounting tape) prepared separately was attached to an 8-inch wafer ring frame and the wafer side of the individualized wafer described above, via the adhesive surface of the dicing tape, using a wafer mounter (manufactured by Nitto Denko Corporation, MSA300). Next, the adhesive film for dicing evaluation was peeled off from the wafer notch with a peeling tape (manufactured by Lasting Systems, PET38REL) using a tape peeler (manufactured by Nitto Denko Corporation, HR3000III). The device peelability was then evaluated. In Table 1, the case where the pre-dicing evaluation adhesive film could be peeled off from the wafer in one go was recorded as "OK."
[0093] In addition, the adhesive residue on the individualized wafers after the pre-dicing method was observed and evaluated using an optical microscope (Olympus Corporation). In particular, the areas where grooves had been formed were observed to see if there were any thread-like adhesive residues. In Table 1, cases where no adhesive residue was observed were recorded as "OK," and cases where adhesive residue was present were recorded as "present."
[0094] Various information is summarized in Table 1. The units of E'(-15°C) and E'(100°C) are Pa.
[0095] [Table 1]
[0096] As shown in Table 1, when manufacturing electronic devices using the pre-dicing method, the occurrence of adhesive residue was suppressed by using an adhesive film having an adhesive resin layer made of an ultraviolet-curable adhesive resin material whose E'(100°C) and E'(100°C) / E'(-15°C) were within appropriate numerical ranges. On the other hand, when manufacturing electronic devices using the pre-dicing method, when an adhesive film was used having an adhesive resin layer made of an ultraviolet-curable adhesive resin material in which part or all of E'(100°C) and E'(100°C) / E'(-15°C) were not within the appropriate numerical range, adhesive residue occurred.
[0097] This application claims priority based on Japanese Patent Application No. 2021-090297, filed on May 28, 2021, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]
[0098] 10 Base material layer 20 Adhesive resin layer 30 Wafers 30A circuit forming surface 31 Chips 50 Adhesive Film 100 structures
Claims
1. A step (A) of preparing a structure including a wafer having a circuit formation surface and an adhesive film attached to the circuit formation surface side of the wafer; a step (B) of back-grinding a surface of the wafer opposite to the circuit-formed surface; (C) irradiating the adhesive film with ultraviolet light and then removing the adhesive film from the wafer; A method for manufacturing an electronic device comprising at least The adhesive film comprises a base layer and an adhesive resin layer made of an ultraviolet-curable adhesive resin material and provided on one surface side of the base layer; When the viscoelastic properties of the ultraviolet-curable adhesive resin material were measured by the following procedures (i) and (ii), the storage modulus at −15° C. was E′(−15° C.) and the storage modulus at 100° C. was E′(100° C.): E'(100°C) is 1.0 x 10 6 ~3.5 x 10 7 Pa, E'(100°C) / E'(-15°C) is 2.0 x 10 -3 ~1.5 x 10 -2 The method for manufacturing an electronic device is as follows. [procedure] (i) A film having a thickness of 0.2 mm is formed using the ultraviolet-curable adhesive resin material, and the film is irradiated with ultraviolet light having a dominant wavelength of 365 nm at an irradiation intensity of 100 W / cm using a high-pressure mercury lamp in an environment of 25° C. 2 The UV dose is 1080 mJ / cm 2 The composition is then irradiated with UV light to cure the composition, thereby obtaining a cured film. (ii) The dynamic viscoelasticity of the cured film is measured at a frequency of 1 Hz in a tensile mode at temperatures ranging from -50 to 200°C.
2. 2. A method for manufacturing an electronic device according to claim 1, comprising the steps of: E' (-15°C) is 6.0 x 10 8 ~3.0 x 10 9 A method for manufacturing an electronic device,
3. A method for manufacturing an electronic device according to claim 1 or 2, comprising the steps of: The step (A) At least one step (A1) selected from a step (A1-1) of half-cutting the wafer and a step (A1-2) of irradiating the wafer with a laser to form a modified layer on the wafer; After the step (A1), a step (A2) of attaching the adhesive film to the circuit-formed surface side of the wafer; A method for manufacturing an electronic device comprising the steps of:
4. A method for manufacturing an electronic device according to claim 1 or 2, comprising the steps of: In the step (C), the pressure-sensitive adhesive film is subjected to a pressure-sensitive adhesive energy of 200 mJ / cm 2 More than 2000mJ / cm 2 The adhesive resin layer is photocured by irradiating it with ultraviolet light at a dose below 100 nm to reduce the adhesive strength of the adhesive resin layer, and then the adhesive film is removed from the wafer.
5. A method for manufacturing an electronic device according to claim 1 or 2, comprising the steps of: The adhesive resin layer comprises a (meth)acrylic resin having a polymerizable carbon-carbon double bond in the molecule, and a photoinitiator.
6. A method for manufacturing an electronic device according to claim 1 or 2, comprising the steps of: The method for producing an electronic device, wherein the adhesive resin layer has a thickness of 5 μm or more and 300 μm or less.
7. A method for manufacturing an electronic device according to claim 1 or 2, comprising the steps of: A method for manufacturing an electronic device, wherein the resin constituting the base layer contains one or more selected from the group consisting of polyolefin, polyester, polyamide, poly(meth)acrylate, polyvinyl chloride, polyvinylidene chloride, polyimide, polyetherimide, ethylene-vinyl acetate copolymer, polyacrylonitrile, polycarbonate, polystyrene, ionomer, polysulfone, polyethersulfone, polyetheretherketone, and polyphenylene ether.
Citation Information
Patent Citations
Surface protective sheet
JP2014075560A
Adhesive tape for semiconductor wafer surface protection and method for processing semiconductor wafer
JP2016072546A
Dicing die bonding film
JP2018195746A
Dicing tape, dicing die-bonding film, and method of manufacturing semiconductor device
JP2019016633A
Dicing tape and dicing die bond film
JP2021005623A